Constant Jamming Experimental Results on Indoor Wireless Sensor Network - Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2017)
The interference attack or better known as jamming attacks are very easy to implement affecting the service of any wireless communication system given the vulnerability of data sent to the user. This attack by denying the normal operation of the service detracts from the purpose of these systems. In general, a jamming attack is difficult to detect given the little experimental data provided by the literature. Therefore, the purpose of this work is to present the experimental results obtained from an indoor Wireless Sensor Network in the presence of a constant jamming. The results are based on performance metrics such as Bit Error Rate, Packet Error Rate and Throughput, in order to analyze the behavior of these metrics in the presence of an attack and thus generate ideas to detect and/or combat them. © 2017 IEEE.